The Relationship between Human Capital and Public Services Performance: The Role of Islamic Work Ethics as a Mediating Variable A Case Study of Public Sector Organizations of Bahrain - Busenan, Ebrahim Farhan Mubarak (Technium Social Sciences Journal, 2023)
Ethics are the basis for achieving individual, group and societal happiness. This research paper studies the role of Islamic work ethics as a mediating variable in the relationship between human capital and public services performance in the public sector of Bahrain. The scarcity of previous studies in the field of Islamic work ethics as a mediating variable in the relationship between human capital and public services performance is the motivating factor of this study. A total of 640 questionnaires were distributed to the citizens in the four governorates of Bahrain, i.e., Southern, Muharraq, Northern and the Capital, using the systematic random sampling method, A five point Likert scale was used to measure all variables. A total of 384 questionnaires were returned of which 368 were usable questionnaires. The findings of this research paper show a significant and positive relationship between human capital and public services performance. Islamic work ethics, as the mediating variable, has a highly positive effect on the relationship between human capital and public services performance.